PERBANDINGAN PENGKODEAN TEKS MENGGUNAKAN ALGORITMA HUFFMAN DAN ALGORITMA HUFFMAN WEAVEN HANKAMER PADA APLIKASI MATLAB - Muhammad Abizar Rofi'udin; Beby H. A. Manafe; Amin A. Maggang (Jurnal Media Elektro, 2022)
Huffman Algorithm and Huffman Weaven-Hankamer Algorithm are the two-source coding algorithms applied generally for text coding. Both algorithms consist of many stages to complete the coding processes. The more character to processes, the longer the time they consume. Therefore, this research aimed to create a user interface using MATLAB that can simulate the process of both algorithms and provide highly accurate results faster. There were two scenarios for the experiments. Both approaches were conducted eight times using the same number of characters, 15 to 22 thousand. ELSE characters were also contained in the information sources, but they are different in number compared to ordinary characters. The first experiment used more ELSE characters, whereas the second applied lesser ELSE characters than the ordinary ones. The results showed that the Huffman algorithm was more efficient in the first scenario than Huffman Weaven-Hankamer, which was a 2.24 percent average difference. Although the Huffman algorithm still performed better in the second experiment, the difference in average efficiency was smaller, 1.48 percent, compared to the first approach. In addition, the results also showed that the Huffman weaves Hankamer Tree was simpler than the Huffman tree.